Molecular diagnosis of gastroinstestinal viruses in Iberian Wolf (canis lupus signatus) and stray dogs (canis lupus) in northern Portugal - Maia, Inês Sofia da Costa (Universidade de Lisboa, Faculdade de Medicina Veterinária, 2024)
Dissertação de Mestrado Integrado em Medicina Veterinária, área científica de Sanidade Animal Currently, infectious diseases are considered a major threat to the preservation of biodiversity, with viruses emerging as a primary source of outbreaks in wildlife. Consequently, it becomes crucial to monitor the presence of viruses within animal populations that exhibit an alarming conservation status, such as the Iberian wolf (Canis lupus signatus). Between 2020 and 2021, 214 stool samples were collected in northern Portugal, of which 199 belonged to Iberian wolves and 15 to stray dogs. With these samples, an initial screening was performed using real-time PCR and conventional PCR for the most common viruses in the Iberian wolf, with the following detection frequencies: canine parvovirus (5.0%), canine distemper virus (5.5%), coronavirus (10.0%), and canine adenovirus (13.5%). In this study, the prevalence rates of canine parvovirus, canine distemper virus, and canine adenovirus were found to be higher in the dog samples compared to the wolves’ samples. This finding underscores the significance of stray dogs in the maintenance of these infectious agents in the habitat. Furthermore, eleven animals from two different packs were identified from 63 samples of Iberian wolves. Based on the collected information, the viral exposure of each individual over time and the presence of these agents in the identified packs, were analyzed. By employing a qPCR genotyping technique, three distinct genotypes of canine parvovirus were identified. Furthermore, the sequencing of the partial Np gene from a CDV positive sample enabled its assignment with the European genotype confirming circulation of non-vaccine strains in the study population. It was not possible to sequence positive samples for canine coronavirus or canine adenovirus in order to carry out the phylogenetic analysis of these samples. However, using the partial sequence of E3 gene of the Adenoviridae family, it was possible to confirm for the first time the presence of ...